Analisis Yuridis Tindak Pidana Pencurian dengan Kekerasan Berdasarkan Berita Acara Pemeriksaan (BAP): Studi Kasus Nomor: Lp/B/196/X/2025/Spkt/Polres Malaka/Polda Ntt - Fisensius Samara; Mesi Mertinshe Tolang; Osa Monika Naibahas; Alfonsius Beni Umenebon; Yesaya Marsel Wasington Nesnatun; Daniel Hendrikson Tangpada (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the legal eligibility of this crime to be brought to trial, has fulfilled the Criminal Code Article 365 and the verdict for the case of theft with violence that occurred in the Malaka Police area based on the Investigation Report. The Investigation Report (BAP) has an important position as the main instrument in the process of evidence in the criminal justice system in Indonesia. This study examines the BAP in a case of alleged theft with violence in Malaka Regency with victims AL and the accused M and his friends. Based on the results of the study, all elements of Article 365 of the Criminal Code were proven through the actions of blocking, making threats using sharp weapons, seizing the victim's belongings, and burning a motor vehicle. The initial evidence collected includes statements from victims, witnesses, and evidence showing that the case meets the formal and material requirements to be submitted to court. Juridically and sociologically, the perpetrators deserve to be given severe criminal sanctions as an effort to enforce the law, provide a deterrent effect, and prevent the potential for social conflict in the community.